2019
DOI: 10.1021/acs.orglett.9b01633
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Chiral 1,3-Diamines through Rhodium-Catalyzed Asymmetric Arylation of Cyclic N-Sulfonyl Imines

Abstract: A rhodium/sulfur−olefin complex catalyzed asymmetric 1,2-addition of arylboronic acids to six-membered 1,2,6-thiadiazinane 1,1-dioxide-type cyclic imines to access highly optically active sulfamides (95−99% ee) has been developed. By taking advantage of the simple functional group transformations, an interesting array of valuable chiral 1,3diamines with different substitution patterns can be readily obtained in a highly enantioenriched manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…2 Wu et al reported a rhodium-catalyzed asymmetric 1,2-addition of arylboronic acids to six-membered 1,2,6-thiadiazinane 1,1-dioxide-type cyclic imines to afford highly optically active sulfamides (95-99% ee). 3 High diastereoselectivity and enantioselectivity was observed in a [4 + 2] reaction between cyclic sulfonic imine and Boc-protected indole aldehyde yielding polycyclic pyridoindoles. 4 Aza-Darzens reaction of cyclic N-sulfonylimines with a-halogenated ketones provided a variety of tri-and tetrasubstituted aziridines, including benzofused heterocycles as well as spiro-structures in high yields, diastereo-and enantioselectivities (up to >20 : 1 dr and >99.9% ee).…”
Section: Introductionmentioning
confidence: 99%
“…2 Wu et al reported a rhodium-catalyzed asymmetric 1,2-addition of arylboronic acids to six-membered 1,2,6-thiadiazinane 1,1-dioxide-type cyclic imines to afford highly optically active sulfamides (95-99% ee). 3 High diastereoselectivity and enantioselectivity was observed in a [4 + 2] reaction between cyclic sulfonic imine and Boc-protected indole aldehyde yielding polycyclic pyridoindoles. 4 Aza-Darzens reaction of cyclic N-sulfonylimines with a-halogenated ketones provided a variety of tri-and tetrasubstituted aziridines, including benzofused heterocycles as well as spiro-structures in high yields, diastereo-and enantioselectivities (up to >20 : 1 dr and >99.9% ee).…”
Section: Introductionmentioning
confidence: 99%
“…Through the use of simple chiral olefin ligands, we have developed highly efficient asymmetric addition to cyclic N ‐sulfonyl imines under rhodium catalysis for accessing a broad range of enantiomerically enriched cyclic amines containing multifunctional groups . Quite recently, we reported construction of an interesting array of valuable chiral 1,3‐diamines through rhodium‐catalyzed asymmetric addition of arylboronic acids to six‐membered 1,2,6‐thiadiazinane 1,1‐dioxide‐type cyclic imines . In connection to this success, we envisaged that the construction of α‐quaternary chiral amino acids might be achieved by designing the corresponding 1,2,6‐thiadiazinane 1,1‐dioxide‐type cyclic α‐iminoesters as new substrates under appropriate transition‐metal catalysis (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Representative ligands for the asymmetric arylation reactions of cyclic N -sulfonyl ketimines and/or cyclic N -sulfonyl diketimines reported to date are shown in Figure . In the case of reactions employing chiral rhodium catalysts, the use of diene, , sulfur-olefin, phosphite-olefin, bisphosphine, and bis(phosphoramidite) ligands has been reported. In the case of reactions using chiral palladium catalysts, pyridine-oxazoline, chiral palladium catalysts, phosphine-oxazoline, pyridine-hydrazone, imidazoline palladacycle, phosphine-imine, and bis(imidazoline) ligands have been employed.…”
mentioning
confidence: 99%
“…In the case of reactions using chiral palladium catalysts, pyridine-oxazoline, chiral palladium catalysts, phosphine-oxazoline, pyridine-hydrazone, imidazoline palladacycle, phosphine-imine, and bis(imidazoline) ligands have been employed. Xu reported the first rhodium-catalyzed enantioselective arylation of cyclic N -sulfonyl diketimines, 1,2,5-thiadiazoline 1,1-dioxide derivatives 1 , by employing a sulfinamide-based olefin ligand (Figure ) and achieved high enantioselectivities . Although these studies have contributed substantially to advances in this field, achieving stereocontrol in new catalytic systems remains a daunting challenge.…”
mentioning
confidence: 99%